Characterisation of Thiol-releasing and Lower Volatile Acidityforming Intra-genus Hybrid Yeast Strains for Sauvignon blanc Wine - Hart, R.S.; Ndimba, B.K.; Jolly, N.P. (South African Journal of Enology and Viticulture, 2017)
A single Saccharomyces cerevisiae wine yeast strain produces a range of aroma and flavour metabolites (e.g. volatile thiols), as well as unfavourable metabolites (e.g. volatile acidity [VA]) during the alcoholic fermentation of white wine, especially Sauvignon blanc. The former contributes to the organoleptic quality of the final wine. Previous research showed that yeast derived enzymes (proteins) are involved in the release of wine quality enhancing or reducing metabolites during fermentation. Small-scale winemaking trials were initiated to evaluate protein expression and metabolite release of tropical fruit aroma wine producing S. cerevisiae hybrid yeasts. Commercial ‘thiol-releasing’ wine yeasts (TRWY) were included in winemaking trials as references. Improved hybrids were identified which showed enhanced thiol-releasing, specifically 3-mercaptohexanol (3MH), and lower VA formation during the production of Sauvignon blanc wines compared to some commercial TRWY references. It is noteworthy that the hybrid NH 56 produced wines with the second highest 3MH levels after hybrid NH 84, and lowest acetic acid of all strains included in this study. This yeast was also the only strain to have down-regulated proteins linked to amino acid biosynthesis, pentose phosphate pathway, glycolysis and fructose and galactose metabolism during the lag phase. Furthermore, differences in protein expression were reflected in the variation of metabolite release by different strains, thereby confirming that enzymes (proteins) are the final effectors for metabolite release.